An Evaluation of Microplastics Contamination in Narayani River - Acharya, Dhruba; Neupane, Suraj; Gautam, Riti (Bharatpur Pragya: Journal of Multidisciplinary Studies, 2025)
Plastic pollution has emerged as one of the growing challenges due to their relatively low production cost, unique physiochemical properties, ease in access, and little or no alternatives to its use and its use are not only limited to domestic, institutional, and industrial purpose. This study is conducted to examine the micro plastics (MPs) contamination in the Narayani River - one of the major drainage systems of Nepal. The water samples from the Narayani River were taken from five different locations in the first half of June 2023 covering around seven kilometers (km) of river stretch starting from the upstream of Devghat cremation site, to the downstream near the landfill site. Micro plastics extraction from surface water was be performed with reference to National Oceanic and Atmospheric Administration (NOAA) and criteria described by (Hidalgo-Ruz et al., 2012) was followed to identify micro plastics. In addition, hot needle tests were conducted to confirm whether the suspected particles were plastic or non-plastic. Results indicate, five different types of MPs namely, fiber, pellet, film, foam and fragment. A total number of 81 particles throughout the surface water samples of Narayani River. On average 0.53 particle per liter of fibers were found followed by film, fragments, foam and pallets with value of 0.16, 0.08, 0.03 and 0.01 particle per liters respectively. Lack of awareness, inefficient waste management, and municipal solid waste dumping together with increased urbanization were some of the major contributors to the MPs pollution in Narayani River.